Evaluation Community Satisfaction Evaluation of the Universitas Singaperbangsa Karawang Community Service Program (KKN) Implementation in Sindangsari Village, Bekasi: Evaluasi Tingkat Kepuasan Masyarakat terhadap Pelaksanaan KKN Universitas Singaperbangsa Karawang di Desa Sindangsari, Bekasi - Sarah Dampang; Endah Purwanti; Vita Efelina; Azafilmi Hakiim (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Community Service Program (KKN) activities are a form of student service to the community that aims to support village development based on local potential. Universitas Singaperbangsa Karawang carries out a KKN program in Sindangsari Village, Cabangbungin District, Bekasi Regency, with various educational and social activities. This article aims to evaluate the level of public satisfaction with the implementation of the KKN program. The method used was a quantitative descriptive survey by distributing questionnaires to 40 respondents from eight hamlets in Sindangsari Village. The results of the study show that the majority of people are satisfied with the implementation of KKN, especially in the aspects of student ethics, the usefulness of the program, and the involvement of residents in activities. These findings show that KKN activities have made a positive contribution to the community and become an evaluative basis for the development of programs in the future.